Astragaloside IV Protects Ethanol-Induced Gastric Mucosal Injury by Preventing Mitochondrial Oxidative Stress and the Activation of Mitochondrial Pathway Apoptosis in Rats - Qin, Shumin; Yin, Jinjin; Huang, Shaogang; Lin, Jingyu; Fang, Zhigang; Zhou, Yunsong; Huang, Keer (Frontiers in Pharmacology, 2019)
Alcohol consumption affects gastric mucosa by multiple and complex mechanisms depending either by direct contact of ethanol or by indirect biological damage induced by its metabolite acetaldehyde. The present study aims at further investigating the mechanism of ethanol-induced gastric mucosa injury and the protective effect of astragaloside IV (AS-IV) in an aspect of mitochondrial oxidative stress and mitochondrial pathway of apoptosis. Using an array of experimental approaches, we have shown that the development of mitochondrial oxidative stress and associated apoptosis play crucial roles in the pathogenesis of gastric injury induced by ethanol. AS-IV inhibits mitochondrial oxidative stress by scavenging accumulation of malondialdehyde and decreasing the consumption of glutathione. AS-IV also prevents the ethanol-induced apoptosis by modulating the activity of caspase-3 and caspase-9, the expression of Bax/Bcl-2 and the release of cytochrome C and apoptosis inducing factor. Moreover, AS-IV reduces ethanol-mediated activation of caspase-8 and breakage of Bid. This study thus indicates that AS-IV prevented ethanol-induced gastric damage by blocking activation of mitochondrial oxidative stress and mitochondrial pathway of apoptosis induced by ethanol in the gastric mucosa.